Urrets-Zavalia syndrome as a complication of argon laser peripheral iridoplasty. Issue 4 (20th September 2006) - Espana, E M; Ioannidis, A; Tello, C; Liebmann, J M; Foster, P; Ritch, R
Abstract : Objective: To report on 8 patients who developed prolonged mydriasis after argon laser peripheral iridoplasty (ALPI). Design: Retrospective case series. Methods: A review of the charts of 8 patients with persistent occludable angles after laser iridotomy who developed mydriasis after undergoing ALPI. Results: 12 eyes of 8 patients (mean age 50.2, standard deviation 6.9, range 40–61 years) developed persistent dilatation. 7 of 8 patients had plateau iris syndrome. Only one patient had a decrease in visual acuity. Intraocular pressure increased only in 1 eye and remained stable or decreased in the others. Of the 8 patients, 7 had blurred vision, 2 had photophobia, 4 had glare and 1 had discomfort. The pupillary response to pilocarpine instillation was minimal or absent. Mydriasis eventually resolved in all eyes without treatment. Conclusion: ALPI can be complicated by mydriasis unresponsive to pilocarpine. Mydriasis and accompanying symptoms resolved spontaneously within 1 year in most patients.